2008
DOI: 10.1186/1471-2318-8-36
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, dementia and cognitive decline in the elderly, a systematic review

Abstract: Background: Nicotine may aid reaction time, learning and memory, but smoking increases cardiovascular risk. Cardiovascular risk factors have been linked to increased risk of dementia. A previous meta-analysis found that current smokers were at higher risk of subsequent dementia, Alzheimer's disease, vascular dementia and cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
185
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(197 citation statements)
references
References 53 publications
10
185
2
Order By: Relevance
“…Numerous studies have compared current, former and never smokers, but few if any studies have examined duration of smoking cessation. Finally, most studies investigating the effect of smoking on dementia were conducted with Western populations,13, 17 with relatively few studies conducted in Asia. As there are differences in prevalence18 and type distribution19 of dementia among Western and Asian populations, the effect of smoking on the risk of dementia might also differ between ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have compared current, former and never smokers, but few if any studies have examined duration of smoking cessation. Finally, most studies investigating the effect of smoking on dementia were conducted with Western populations,13, 17 with relatively few studies conducted in Asia. As there are differences in prevalence18 and type distribution19 of dementia among Western and Asian populations, the effect of smoking on the risk of dementia might also differ between ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…63 Our PAR calculations used a RR of 1.59 for AD since this was based on the most comprehensive meta-analysis. 64 Former smoking was not associated with AD risk in most studies. 62 Prevalence-The worldwide prevalence of smoking in individuals aged 15 years or older in 1995 was 29%, with the highest prevalence observed in Europe and Asia (34%) and the lowest in sub-Saharan Africa (18%).…”
Section: Smokingmentioning
confidence: 99%
“…[62][63][64] A meta-analysis of 19 prospective studies found that current smoking was associated with a significantly increased risk of dementia (RR, 1.27; 95% CI: 1.02, 1.60) and AD (RR, 1.79; 95% CI: 1.43, 2.23). 62 However, a more recent meta-analysis that included 23 longitudinal studies found slightly lower risk estimates of 1.16 (95% CI: 0.90, 1.50) for all-cause dementia and 1.59 (95% CI: 1.15, 2.20) for AD.…”
Section: Smokingmentioning
confidence: 99%
“…A previous study using the data on adult women in the National Health and Nutrition Survey of Japan (NHNS) from 1989-2003, showed that anemia was prevalent (25.3%-26.2%) among women aged 70 years and older [7]. Recently, studies have indicated anemia as one of the factors responsible for health decline among the elderly, such as increased risk in all-cause mortality [8][9][10][11], decline in cognitive function, dementia [12] and increased fracture risk [13].…”
Section: Introductionmentioning
confidence: 99%